2022
DOI: 10.3390/ijerph19042325
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Photodynamic Coatings Reduce the Microbial Burden on Environmental Surfaces in Public Transportation—A Field Study in Buses

Abstract: Millions of people use public transportation daily worldwide and frequently touch surfaces, thereby producing a reservoir of microorganisms on surfaces increasing the risk of transmission. Constant occupation makes sufficient cleaning difficult to achieve. Thus, an autonomous, permanent, antimicrobial coating (AMC) could keep down the microbial burden on such surfaces. A photodynamic AMC was applied to frequently touched surfaces in buses. The microbial burden (colony forming units, cfu) was determined weekly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 56 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…The field study was performed in two hospitals for several months and the results of the study clearly proved that the novel photodynamic coating significantly reduced the bacterial burden on patient-near surfaces, which may reduce the risk of nosocomial transmission of pathogens (18). Unfortunately, despite the advantages of PDI coatings and its proven efficacy in field studies (18,(20)(21)(22), the use of silver, copper and quaternary ammoniums are reported to be the major technologies so far, whereas the role of PDI is almost unmentioned (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…The field study was performed in two hospitals for several months and the results of the study clearly proved that the novel photodynamic coating significantly reduced the bacterial burden on patient-near surfaces, which may reduce the risk of nosocomial transmission of pathogens (18). Unfortunately, despite the advantages of PDI coatings and its proven efficacy in field studies (18,(20)(21)(22), the use of silver, copper and quaternary ammoniums are reported to be the major technologies so far, whereas the role of PDI is almost unmentioned (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the effect of photodynamic AMC on the microbial burden of frequently touched surfaces in public buses was investigated using the plating method. The results showed that photodynamic AMC kept the microbial load low and significantly reduced the risk of microbial transfer (Kalb et al, 2022). Numerous studies have applied traditional, culture-based microbial surveys, and the results have provided basic information about the microbial burden levels on different surfaces.…”
Section: Detecting Microbes Using Traditional Methodsmentioning
confidence: 99%
“…There have been many attempts to provide solutions to this task including antimicrobial coatings, films, or surfaces that can further reduce the spread of the infectious pathogens for prolonged periods of time. [4][5][6][7][8] Chang et al (2019) 9 used natural resin from coniferous pine tree to blend with synthetic polymer (Poly(ε-caprolactone) (PCL)) to take advantage of the highly antimicrobial property of the natural resin and create a more sustainable composite. Authors presented encouraging results suggesting that the new blends at 50% by weight still possess antimicrobial properties against four strains of bacteria (S. aureas, E. coli, B. subtilis, and P. aeruginosa).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed a 25% reduction in bacteria colony counts. 7 Hardison et al has evaluated the residual efficacy of quaternary ammonium compounds (QACs) against SARS-CoV-2 on stainless steel and on acrylonitrile butadiene styrene (ABS) plastic. Their study demonstrated that some commercial products showed 1.67 to 3-log reductions against SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%